Nature as Evidence: On Ibn Rushd's Theorems for God's Existence - Alya Mumtaza Hafidz (The Ulama Cadre Education Program of Great Mosques of Istiqlal (PKUMI), 2024)
The complexity of nature and its beauty have been inspiring some philosophers to postulate argument for God’s existence. In his endavour to comment on mutakallimun’s argumentations, which contained with many falsehood, Ibn Rushd offerred two simple alternative theorems that he deduced from Quranic verses and nature’s complexity. These theorems was shown in Kitab Al-Kasyf ‘an Manahij al-Adilla fi ‘Aqa’id al-Milla which Ibn Rushd called dalil Inayah and dalil Ikhtira. Not only came from Muslim side, these theorems apparently have some similarity with argumentations that proposed by Western thinkers in modern era; argument from Anthropic principles and William Paley’s Watchmaker argument. Based on those similarity, this research aims to compare and to show some logical fallacies along with objections toward Ibn Rushd’s theorems and Western thinker’s arguments. Through library research, researchers have found some weakness in both type of arguments; such as fallacy of false cause, special pleading fallacy, false analogy, and even emerged bigger consequence from the problem of evil. With these flaws and logical fallacies, Ibn Rushd’s theorems and Western’s argumentations for God’s existence that based on nature’s empirical evidences should not be sustained any longer.